2022
DOI: 10.1128/aem.01873-21
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Degradation of Medium-Chain-Length Dicarboxylic Acids in Cupriavidus necator H16 Reveal β-Oxidation Differences between Dicarboxylic Acids and Fatty Acids

Abstract: Many homologous genes encoding β-oxidation enzymes were found in the genome of Cupriavidus necator H16 (synonym: Ralstonia eutropha H16). By proteome analysis, the degradation of adipic acid was investigated and showed differences to the degradation of hexanoic acid. During β-oxidation of adipic acid, activation with coenzyme A (CoA) is catalyzed by the two-subunit acyl-CoA ligase encoded by B0198 and B0199. The operon is completed by B0200 encoding a thiolase ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…The maximal growth rates achieved for the four species with the optimised media (MSM with sebacic acid) were 0.267 ± 0.08 h −1 , 0.243 ± 0.023 h −1 , 0.112 ± 0.004 h −1 , and 0.118 ± 0.005 h −1 for H. aestusnigri, H. bauzanensis, H. litoralis, and H. oceani, respectively. Reported growth rates of the Proteobacteria Cupravidus necator and Pseudomonas nitroreducens on sebacic acid were within a similar range (Janota-Bassalik & Bohdanowicz-Strucinska, 1974;Lang et al, 2007;Strittmatter et al, 2022). From Sullivan et al (2022), approx.…”
Section: Growth Of Halopseudomonas Spp Under Typical Laboratory Condi...mentioning
confidence: 86%
“…The maximal growth rates achieved for the four species with the optimised media (MSM with sebacic acid) were 0.267 ± 0.08 h −1 , 0.243 ± 0.023 h −1 , 0.112 ± 0.004 h −1 , and 0.118 ± 0.005 h −1 for H. aestusnigri, H. bauzanensis, H. litoralis, and H. oceani, respectively. Reported growth rates of the Proteobacteria Cupravidus necator and Pseudomonas nitroreducens on sebacic acid were within a similar range (Janota-Bassalik & Bohdanowicz-Strucinska, 1974;Lang et al, 2007;Strittmatter et al, 2022). From Sullivan et al (2022), approx.…”
Section: Growth Of Halopseudomonas Spp Under Typical Laboratory Condi...mentioning
confidence: 86%
“…Metagenomic data results indicated a diversity of microorganisms associated with lipid degradation ( Table 3 ). It was reported that the genome of the related strain C. necator H16 contained many homologs of genes encoding β-oxidases related to the beta-Oxidation reactions that were involved in fatty acid degradation, suggesting that C. necator H16 was considered to be a strong candidate for the production of specific chain-length organic acids ( Strittmatter et al, 2022 ). In addition to its denitrification capability, A. denitrificans K601 exhibited the ability to utilize cyclic lipids as a sole carbon source and organic acids, e.g., lactic acid, acetic acid, and propionic acid, as alternative carbon sources ( Oosterkamp et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%